Antibiotic Use in Livestock and Environmental Antibiotic Resistance: A Narrative Review - Tesfaye Admassu Abate; Alemayehu Godana Birhanu (Environmental Health Insights)
Antimicrobial use in animal husbandry is a common practice in developing countries as a response to the growing demand for animal-based foods. Veterinary antibiotics account for most of the antibiotics used worldwide. This review aims to provide an overview of the impact of antibiotic usage in livestock production on the environment and its consequences in the emergence and spread of antibiotic resistance. The global estimate of antibiotic consumption in animals ranges from 63 000 to 106 000 tons annually. The most commonly used antibiotic classes include tetracyclines, sulfonamides, β-lactams, macrolides, and trimethoprim. Most of the antibiotics used in animal treatments are not fully metabolized within the animal’s body; instead, they are excreted and can enter the environment. This review also provides a brief overview of the fate of antibiotic residues and their behavior in the environment. In developing countries, in addition to the lack of data on antibiotic use trends, there are limitations in implementing scientific and regulatory frameworks for antibiotic use in livestock. To reduce the projected loss of lives associated with antimicrobial resistant infections, it is recommended to lower antibiotic contamination in the environment by implementing affordable and critical actions related to antibiotic usage and residual waste management. Actions such as rational use of antibiotics in all circumstances, reducing environmental exposure to antibiotics, research, and environmental surveillance are important to tackle the problems of antibiotic resistance, especially in low-income countries.